Analysis of novel three-dimensional pole arrays for electromagnetic spherical actuators - Yan, Liang (2013)
Permanent Magnet (PM) array is one of the key factors that influence the output performance of electromagnetic spherical actuators significantly. Conventionally, two-dimension al (2D) PM arrays are widely employed in the design of spherical actuators, which constraints the system torque output greatly. The purpose of this paper is to propose a novel concept of 3D PM array to improve the output performance of spherical actuators. The concept of 3D PM array is illustrated and briefly introduced. The design and analysis of PM array follows the sequence of 1D, 2D and 3D. The influence of major structure parameters on the magnetic field and torque output of spherical actuators are studied subsequently. The proposed PM array can also be implemented into other electromagnetic actuators to improve the force and torque output.